The Symbolic Meaning of Prayer in Islamic Education: Global Research Trends and Alignment with the SDGs - Muhammad Muhtar Arifin Sholeh; Waston; Muhammad Sholahuddin; Qudra Bezibweki; Qisthoni Permatasari (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study aims to examine the symbolic meaning of prayer in Islamic Religious Education through a bibliometric approach, focusing on mapping publication trends, identifying influential authors and journals, and exploring key relevant topics, especially in relation to the Sustainable Development Goals (SDGs) agenda. Theoretical framework: This research relies on the perspective of symbolic interaction that views prayer as a symbolic construction in the formation of character and internalization of spiritual, social, and educational values. This framework is linked to the SDGs, specifically the goals of quality education, social inclusion, and environmental sustainability. Literature review: Previous studies have highlighted the role of Islamic education in character building, the spiritual and symbolic dimensions of prayer, as well as its relationship to global issues such as climate change, sustainability, and the integration of technology in learning. Methods: The research method used bibliometric analysis with the Scopus database for the period 2019–2025. The analysis focused on publication performance, author collaboration, citation networking, and thematic mapping through Bibliometrix and Biblioshiny software to obtain a comprehensive picture of the research landscape. Results: The results of the study show a significant increase in publications related to the symbolic meaning of prayer, with dominant contributions from the United States, the United Kingdom, and Indonesia. The main themes that emerged included Islamic education, sustainability, climate change, and their connection to the SDGs agenda. Implications: This research emphasizes the importance of integrating spirituality and sustainability in Islamic Religious Education, while supporting the development of a value-based curriculum that is aligned with the SDGs agenda, through cross-border and cross-disciplinary collaboration. Novelty: The novelty of this research lies in the use of bibliometric analysis to examine the symbolic meaning of prayer in the context of the SDGs, to be able to map global trends while offering a new direction for interdisciplinary curricula and research.